Nitrogen use efficiency is regulated by interacting proteins relevant to development in wheat. Issue 6 (15th January 2018) - Lei, Lei; Li, Genqiao; Zhang, Hailin; Powers, Carol; Fang, Tilin; Chen, Yihua; Wang, Shuwen; Zhu, Xinkai; Carver, Brett F.; Yan, Liuling
Summary: Wheat ( Triticum aestivum ) has low nitrogen use efficiency (NUE). The genetic mechanisms controlling NUE are unknown. Positional cloning of a major quantitative trait locus for N‐related agronomic traits showed that the vernalization gene TaVRN‐A1 was tightly linked with TaNUE1, the gene shown to influence NUE in wheat. Because of an Ala 180 /Val 180 substitution, Ta VRN‐A1a and Ta VRN‐A1b proteins interact differentially with Ta ANR1, a protein encoded by a wheat orthologue of Arabidopsis nitrate regulated 1 ( ANR1 ). The transcripts of both TaVRN ‐ A1 and TaANR1 were down‐regulated by nitrogen. TaANR1 was functionally characterized in TaANR1::RNAi transgenic wheat, and in a natural mutant with a 23‐bp deletion including 10‐bp at the 5′ end of intron 5 and 13‐bp of exon 6 in gDNA sequence in its gDNA sequence, which produced transcript that lacked the full 84‐bp exon 6. Both Ta ANR1 and Ta HOX1 bound to the Ala 180 /Val 180 position of Ta VRN‐A1. Genetically incorporating favourable alleles from TaVRN‐A1, TaANR1 and TaHOX1 increased grain yield from 9.84% to 11.58% in the field. Molecular markers for allelic variation of the genes that regulate nitrogen can be used in breeding programmes aimed at improving NUE and yield in novel wheat cultivars.